PEMANFAATAN ANIMASI PLOTAGON UNTUK MENINGKATKAN ANTUSIASME SISWA DALAM MATA PELAJARAN BAHASA INDONESIA - MEIYEN DWI REJEKI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The purpose of this research is to increase students' enthusiasm in learning Indonesian by utilizing plotagon animation. Negotiation material is a material that must be practiced so that students understand better, but online learning conditions so teachers must be able to make negotiation materials with online conditions that are interesting and easy to understand. From these problems the authors are interested in conducting research with the title